Data from: Higher rates of pre‐breeding condition gain positively impacts clutch size: a mechanistic test of the condition‐dependent individual optimization model ... - Hennin, Holly L.; Dey, Cody J.; Bety, Joel; Gilchrist, H. Grant; Legagneux, Pierre; Williams, Tony D.; Love, Oliver P. (Dryad, 2019)
1. A combination of timing of and body condition (i.e., mass) at arrival on the breeding grounds interact to influence the optimal combination of the timing of reproduction and clutch size in migratory species. This relationship has been formalized by Rowe et al. in a condition-dependent individual optimization model (American Naturalist, 1994, 143, 689-722), which has been empirically tested and validated in avian species with a capital-based breeding strategy. 2. This model makes a key, but currently untested prediction; that variation in the rate of body condition gain will shift the optimal combination of laying date and clutch size. This prediction is essential because it implies that individuals can compensate for the challenges associated with late timing of arrival or poor body condition at arrival on the breeding grounds through adjustment of their life history investment decisions, in an attempt to maximize fitness. 3. Using an 11-year data set in arctic-nesting common eiders (Somateria ... : Hennin-Fattening_Rate_and_Clutch_Size_in_Common_EiderThese data were collected from 2003-2014 at East Bay Island, Southampton Island, Nunavut, Canada. These are data from pre-recruiting, wild-living female common eiders with metrics collected at arrival on the breeding grounds, reproductive outputs, and physiological fattening measured in the lab. ...